Enterprise competitiveness in the digital economy - Sunigovets, Olga (My University, 2019)
Digital economy is the direction of innovation, competitiveness and economic development of corporate structures. The rapid development of digital technology covers all areas of socio-economic activity. On the basis of digital technologies, new digital business models are being created, existing operational models are being transformed, and fundamentally new types of business are being formed. Digital capital becomes a factor in business competitiveness. The main factor of economic development is associated with the digital economy. Digital economy contributes to the formation of new business models.
Keywords: digital economy; finance; enterprise competitiveness; innovation; business models